Desarrollo de las inteligencias múltiples en los niños de sub nivel 2 de la unidad educativa 24 de junio, con el uso de materiales reciclados - Chernez Garzón, Kerlly Alicia (2021)
In this research we try to make known that there are different types of multiple intelligences, and most of the teachers do not know and this causes the learning process in the students of sub-level 2 of the June 24 school to be delayed and not it is known what their strengths in education may be one of the factors that help to develop and know multiple intelligences is the use of didactic materials because these allow students to have new experiences and can work for themselves, in addition to that You can practice from home and study at the same it